Ten thousand horses : how leaders harness raw potential for extraordinary results - Stahl-Wert, John (Berrett-Koehler Publishers, 2007)
Extensive speaking schedule: The authors both average two speaking and/or training engagements per week at major corporate gatherings and at social sector conferences with audiences ranging from 50 to 1000.